The Effect of Strength-Based Parenting, Religious Commitment, Demographic Factors Mediated by Positive Affect on Students' Character Strength - Dewitri Ulfha Ratnasari (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to determine the effect of strength-based parenting and religious commitment on students' character strengths mediated by positive affect. This study uses quantitative methods. The sampling technique was a non-probability and purposive sampling technique. The subjects of this study were 484 students of Senior High School X. The scale used is VIA-72, SBP scale, MUDRAS, and NAPAS. Data were analyzed by path analysis technique using Lisrel 8.80. Based on the results of the analysis showed that the model